AKTIVITAS ANTIOKSIDAN DAN TOKSISITAS EKSTRAK ETHANOL DAUN BALAKACIDA (Chromolaena odorata L.) - Marsella, Virna Rindra; Aswat, Muhammad Raihan; Erwin, Erwin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
This study aims to determine the content of secondary metabolites and toxicity and antioxidants in Balakacida leaf (Chromolaena odorata L.). The dried Balakacida (Chromolaena odorata L.) leaf samples were extracted through maceration process using 96% ethanol solvent and the maceration filtrate was concentrated using rotary evaporator. Furthermore, the crude extract obtained was carried out phytochemical testing, toxicity test with BSLT method and antioxidant test with DPPH method. Phytochemical results of crude extracts of Balakacida leaf isolates (Chromolaena odorata L.) are positive for alkaloids, steroids, triterpenoids, flavonoids, phenolics and quinones. The results of the BSLT method toxicity test obtained an LC50 value of 42.77 ppm which indicates a very strong level of toxicity. The results of the antioxidant test obtained the actual IC50 value of 31.226 ppm indicate that the Balakacida leaf isolate (Chromolaena odorata L.) has very high antioxidant activity. Based on the results of the antioxidant test, Balakacida leaves (Chromolaena odorata L.) have potential as an antioxidant plant. Keywords : Antioxidant, Balakacida, Toxicity, Chromolaena odorata L